Light and magnetism dual-gated photoinduced electron transfer-reversible addition–fragmentation chain transfer (PET-RAFT) polymerization. Issue 12 (13th February 2020) - Hu, Lingjuan; Wang, Qi; Zhang, Xiaomeng; Zhao, Haitao; Cui, Zhe; Fu, Peng; Liu, Minying; Liu, Nan; He, Shengbao; Pang, Xinchang; Qiao, Xiaoguang
Abstract : PET-RAFT polymerization can be reversibly ceased in the absence of light or under an external magnetic field with a novel raspberry-like γ-Fe2 O3 @CD nanocatalyst. Abstract : A novel raspberry-like γ-Fe2 O3 @carbon dot (CD) nanocatalyst was prepared and applied for photoinduced electron transfer-reversible addition–fragmentation chain transfer (PET-RAFT) polymerization. The nanocatalyst was found to be an efficient photocatalyst in visible light-regulated PET-RAFT polymerization owing to the oxidative quenching mechanism between the photoexcited γ-Fe2 O3 @CDs and the RAFT agent in the PET process. Notably, polymerization can be reversibly ceased in the absence of light or under an external magnetic field. The superparamagnetic nature and high saturation magnetization value (∼30.4 emu g −1 ) of the nanocatalyst contribute to convenient recycling of the nanocatalyst after polymerization. The PET-RAFT polymerization with the nanocatalyst before and after recycling was investigated, which displayed all the characteristics of controlled/living polymerization systems.